Electrolyte-resistant composite aluminum foil, current collector and battery
By setting a barrier layer in the composite aluminum foil to regulate stress distribution and increase density, the problem that the conductive layer is prone to fall off in the electrolyte environment is solved, and the cycle life of the battery is improved.
Patent Information
- Application Number
- CN202421220039.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2034-05-30
AI Technical Summary
The existing composite aluminum foil is prone to conduction layer fall off in the electrolyte environment, affecting the battery cycle life.
Several conductive layers are symmetrically arranged on the upper and lower sides of the flexible substrate, and barrier layers are arranged between adjacent conductive layers. The barrier layers can interrupt grain growth, reduce stress concentration and defects, and increase film layer density.
The adhesion between the conductive layer and the polymer film is improved, the weather resistance of the composite aluminum foil is enhanced, and its service life is extended, thereby improving the cycle life of the battery.
Smart Images

Figure CN222619771U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of batteries, in particular to an electrolyte-resistant composite aluminum foil, a current collector and a battery. Background Art
[0002] Traditional batteries use aluminum foil and copper foil as current collectors for positive and negative electrodes, and their disadvantages are that the current collectors are thick, costly, and have low safety and energy density. Because they are composed of pure metals and have the characteristics of brittleness and low toughness, they are prone to breakage and edge damage in the process of coating, rolling, drying, slicing, and other processes under heat and tension in the production process of lithium-ion battery electrode materials, which can easily lead to material waste, poor product consistency, and reduced production efficiency. Therefore, pure metal current collectors are no longer the best application carriers due to key factors such as cost, safety, and energy density. In recent years, many studies have begun to focus on replacing traditional metal current collectors with lightweight flexible metallized plastic composite film materials, that is, a composite current collector is obtained by setting a conductive layer on the surface of a low-density polymer film, so as to achieve higher safety, higher volume energy density, and higher mass energy density of lithium batteries. At present, composite aluminum foils based on polymer substrates have been widely studied and applied in mass production.
[0003] The elastic modulus of the polymer substrate is lower than that of aluminum metal, so the composite aluminum foil using a polymer substrate also has better bending resistance. However, compared with traditional metal foils, the conductive metal aluminum layer of this composite current collector is thinner, and it is more prone to corrosion in the electrolyte environment than traditional metal aluminum foil. Especially during the battery cycle, as the battery electrode expands, the composite current collector may have the phenomenon of falling off of the surface conductive layer, thereby affecting the battery cycle life.
[0004] To solve the above problems, it is necessary to improve the adhesion between the conductive layer of the composite aluminum foil and the polymer film, increase the density of the conductive layer, and improve the overall weather resistance of the film. When the conductive layer is deposited on the surface of the polymer film, the film will generate internal stress due to ion bombardment, interface mismatch, film growth phase change stress, thermal stress and other reasons. After the deposition is completed, the internal stress of the polymer film will be partially released through plastic deformation of the film and the disappearance of film defects over time. As the internal stress is partially released, the internal stress of the polymer film gradually decreases, which in turn leads to a decrease in the shear stress acting at the interface of the polymer film-conductive layer, resulting in low adhesion between the conductive layer and the polymer film, which in turn leads to the shearing of the surface conductive layer of the composite current collector during the processing of the pole piece and the life cycle of the lithium-ion battery. Utility Model Content
[0005] The technical problem to be solved by the utility model is: to overcome the deficiencies in the prior art and provide an electrolyte-resistant composite aluminum foil, a current collector and a battery. In the utility model, a plurality of conductive layers are symmetrically arranged on the upper and lower sides of the flexible substrate, and a barrier layer is arranged between two adjacent conductive layers; the barrier layer can interrupt the growth of grains, reduce stress concentration and defects, increase the density of the film layer, improve the weather resistance of the film layer as a whole, and improve the service life of the composite aluminum foil, and indirectly improve the cycle life of the battery.
[0006] The technical solution adopted by the utility model to solve its technical problems is:
[0007] An electrolyte-resistant composite aluminum foil comprises a flexible substrate, wherein a plurality of conductive layers are symmetrically arranged on the upper and lower sides of the flexible substrate, and a barrier layer is arranged between two adjacent conductive layers;
[0008] The thickness of the flexible substrate is 3 to 20 μm, the thickness of the conductive layer is 200 to 400 nm, and the thickness of the barrier layer is 1 to 10 nm;
[0009] The flexible substrate is one of biaxially oriented polypropylene film (OPP), cast polypropylene film (CPP), polyethylene terephthalate film (PET), polyimide film (PI) and polyethylene naphthalate film (PEN);
[0010] The conductive layer is one of a metal aluminum layer, an aluminum-silicon (AL-Si) alloy layer, an aluminum-copper (Al-Cu) alloy layer, an aluminum-magnesium (Al-Mg) alloy layer, and an aluminum-zinc (Al-Zn) alloy layer;
[0011] The barrier layer is one or at least two of a metal nickel layer, a metal chromium layer, a nickel-chromium (Ni-Cr) alloy layer, a metal titanium layer, a titanium alloy layer, and an aluminum oxide layer.
[0012] The electrolyte-resistant composite aluminum foil also includes a base layer, which is arranged between the flexible substrate and the conductive layer; the base layer has a thickness of 1 to 10 nm and is an aluminum oxide layer.
[0013] Furthermore, the conductive layer is a metal aluminum layer, and the thickness of the conductive layer is 300-350 nm.
[0014] Furthermore, the barrier layer is a nickel-chromium alloy layer.
[0015] Furthermore, three conductive layers are symmetrically arranged on the upper and lower sides of the flexible substrate.
[0016] A current collector comprises a positive electrode and a negative electrode, wherein the positive electrode is the electrolyte-resistant composite aluminum foil, and the negative electrode is a copper foil with a thickness of 6 μm.
[0017] A battery comprises the above-mentioned current collector.
[0018] The beneficial effects of the utility model are as follows: the utility model has a simple structure, a reasonable design, and has the following advantages:
[0019] (1) A base layer is provided between the flexible substrate and the conductive layer. The base layer provides a surface suitable for thin film growth for the conductive layer, which is helpful for the nucleation and growth of the conductive layer. The base layer can promote the uniform growth of the conductive layer and improve the crystallization quality of the conductive layer.
[0020] (2) A barrier layer is provided between two adjacent conductive layers. The barrier layer can help regulate the stress distribution in the conductive layer. By interrupting grain growth, it promotes grain refinement of the conductive layer, thereby increasing the grain boundary size of the conductive layer, thereby dispersing the internal stress of the conductive layer and reducing defects caused by stress concentration. At the same time, since the lattice constants of the barrier layer and the conductive layer are different, the residual stress of the conductive layer can be effectively adjusted by optimizing the material, thereby reducing the performance degradation of the conductive layer caused by stress. After adding the barrier layer, the grain size of the overall conductive layer is smaller and there are more grain boundaries, which can improve the resistance of the composite aluminum foil to corrosive environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the utility model or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the utility model. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 It is a structural schematic diagram of the electrolysis-resistant composite aluminum foil in the utility model.
[0023] In the figure: 1. Flexible substrate, 2. Base layer, 3. Conductive layer, 4. Barrier layer. DETAILED DESCRIPTION
[0024] It should be noted that the following detailed descriptions are all illustrative and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0026] The technical solution of the utility model will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments of the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.
[0027] like Figure 1 The electrolyte-resistant composite aluminum foil shown includes a flexible substrate 1, a plurality of conductive layers 3 are symmetrically arranged on the upper and lower sides of the flexible substrate 1, and a barrier layer 4 is arranged between two adjacent conductive layers 3; the thickness of the flexible substrate 1 is 3 to 20 μm, the thickness of the conductive layer 3 is 200 to 400 nm, and the thickness of the barrier layer 4 is 1 to 10 nm; the flexible substrate 1 is one of a biaxially oriented polypropylene film, a cast polypropylene film, a polyethylene terephthalate film, a polyimide film and a polyethylene naphthalate film; the conductive layer 3 is one of a metal aluminum layer, an aluminum-silicon alloy layer, an aluminum-copper alloy layer, an aluminum-magnesium alloy layer and an aluminum-zinc alloy layer; the barrier layer 4 is one of a metal nickel layer, a metal chromium layer, a nickel-chromium alloy layer, a metal titanium layer, a titanium alloy layer, and an aluminum oxide layer or at least two thereof.
[0028] The electrolyte-resistant composite aluminum foil further comprises a base layer 2, which is arranged between the flexible substrate 1 and the conductive layer 3; the base layer 2 has a thickness of 1 to 10 nm and is an aluminum oxide layer.
[0029] The function of the base layer 2 is to provide a surface suitable for thin film growth for the conductive layer 3, which is helpful for the nucleation and growth of the conductive layer 3. The base layer 2 can promote the uniform growth of the conductive layer 3 and improve the crystal quality of the conductive layer 3.
[0030] Function of barrier layer 4: barrier layer 4 can help regulate stress distribution in conductive layer 3, by interrupting grain growth of conductive layer 3, promoting grain refinement of conductive layer 3, and then increasing grain boundary size of conductive layer 3, thereby dispersing internal stress of conductive layer 3, and reducing defects caused by stress concentration. At the same time, since the lattice constants of barrier layer 4 and conductive layer 3 are different, the residual stress of conductive layer 3 can be effectively adjusted by optimizing materials, thereby reducing performance degradation of conductive layer 3 caused by stress. After adding barrier layer 4, the grain size of the overall conductive layer 3 is smaller and there are more grain boundaries, which can improve the resistance of electrolyte-resistant composite aluminum foil to corrosive environments.
[0031] The conductive layer 3 is a metal aluminum layer, and the thickness of the conductive layer 3 is 300-350 nm.
[0032] The barrier layer 4 is a nickel-chromium alloy layer.
[0033] Three conductive layers 3 are symmetrically arranged on the upper and lower sides of the flexible substrate 1 .
[0034] In the preparation process of this electrolyte-resistant composite aluminum foil, the preparation of the coating structure gives priority to evaporation, sputtering and chemical vapor deposition (CVD) in a high vacuum environment. These methods can achieve precise control of the thickness, composition and microstructure of the coating film, thereby meeting complex functional requirements and demanding application scenarios. In order to further improve the production efficiency and large-scale production capacity of the product, it is preferred to use the evaporation method in physical vapor deposition, namely PVD evaporation. This is because the PVD evaporation method has the characteristics of high efficiency and large-area continuous deposition while maintaining the high quality of the film, which greatly improves the production efficiency and production capacity.
[0035] The preparation method of the above electrolyte resistant composite aluminum foil is as follows:
[0036] Step 1: In a closed chamber of the equipment, a flexible substrate 1 that has been finely processed in advance to remove impurities and enhance adhesion is installed on the unwinding roller in the unwinding chamber, and is gradually connected to the winding roller by a precise winding method to ensure that the substrate is straight, stable and free of wrinkles and twists during the entire coating process;
[0037] Step 2: Different materials used to construct the multifunctional composite film layer, including the base layer S1, the first conductive layer S2, the first barrier layer S3, the second conductive layer S4, the second barrier layer S5 and the final third conductive layer S6, are precisely placed one by one in the six independent evaporation boat positions arranged in sequence in the chamber, namely C1, C2, C3, C4, C5 and C6; the evaporation boats are arranged closely adjacent to each other so as to facilitate the sequential deposition of each functional layer during the coating process.
[0038] Step 3: Adjust the distance between the target material and the surface of the flexible substrate 1 to 30 cm to ensure the best film thickness distribution and film quality. After completing all key parameter settings, close all the sealing doors of the chamber, start the fore pump and molecular pump system, and gradually reduce the vacuum degree in the chamber to the target value of 5×10 -4 Pa; when the ultra-high vacuum state is reached, a specific proportion of process gas is added in time to further adjust to the required process vacuum level;
[0039] Step 4: The preparation work is completely ready, and the evaporation boat power supply can be turned on and the drive roller can be turned on to start the coating process; during this period, the winding speed is strictly controlled to be maintained at 10 to 30 meters per minute; ensure that each layer of film material can be uniformly and continuously deposited on the flexible substrate 1 at the set speed, thereby forming a multi-layer film structure with excellent performance and stability;
[0040] Step 5: Repeat steps 1 to 4 to complete the preparation process of the base layer 2, the conductive layer 3 and the barrier layer 4 on the other side of the flexible substrate 1.
[0041] The above step 4 specifically includes the following steps:
[0042] Step 41: Pre-treatment process of the flexible substrate 1:
[0043] Argon gas is introduced into the vacuum chamber, and the argon gas is ionized by providing 800 W of power to the ion source, thereby cleaning the surface of the substrate;
[0044] Step 42: Formation of the bottom layer S1:
[0045] Argon and oxygen with a purity of not less than 99.99% are introduced into C1, the amount of argon is 400 sccm, and the amount of oxygen is 100 sccm, and a base layer S1 (Al2O3) is formed on the flexible substrate 1 by thermal evaporation using an evaporation boat; the power of the evaporation boat is 10-15Kw;
[0046] Step 43: Formation of the conductive layer S2:
[0047] After the base layer S1 is formed, argon gas with a purity of not less than 99.99% is introduced into C2, and the amount of argon gas is 400 sccm. The corresponding material is formed into a conductive layer S2 on the base layer S1 by thermal evaporation. The power of the evaporation boat is 20-40Kw.
[0048] Step 44: Formation of barrier layer S3:
[0049] Argon gas with a purity of not less than 99.99% is introduced into C3 at a volume of 400 sccm, and the corresponding material is formed into a barrier layer S3 on the conductive layer S2 by thermal evaporation using an evaporation boat; the power of the evaporation boat is 5 to 15 Kw;
[0050] Step 45: Formation of conductive layer S4:
[0051] After the barrier layer S3 is formed, argon gas with a purity of not less than 99.99% is introduced into C4, and the amount of argon gas is 400 sccm. The corresponding material is formed into a conductive layer S4 on the barrier layer S3 by thermal evaporation. The power of the evaporation boat is 20-40Kw.
[0052] Step 46: Formation of barrier layer S5:
[0053] Argon gas with a purity of not less than 99.99% is introduced into C5 at a volume of 400 sccm, and the corresponding material is formed into a barrier layer S5 on the conductive layer S4 by thermal evaporation using an evaporation boat; the power of the evaporation boat is 5 to 15 Kw;
[0054] Step 47: Formation of conductive layer S6:
[0055] After the barrier layer S5 is formed, argon gas with a purity of not less than 99.99% is introduced into C4, and the amount of argon gas is 400 sccm. The corresponding material is formed into a conductive layer S6 on the barrier layer S5 by thermal evaporation; the power of the evaporation boat is 20 to 40 Kw.
[0056] A current collector comprises a positive electrode and a negative electrode, wherein the positive electrode is the electrolyte-resistant composite aluminum foil, and the negative electrode is a copper foil with a thickness of 6 μm.
[0057] A method for preparing a battery is as follows:
[0058] Step 1: Material preparation:
[0059] Positive electrode material: lithium iron phosphate (LiFePO4);
[0060] Anode material: graphite;
[0061] Diaphragm: polypropylene (PP) or polyethylene (PE);
[0062] Electrolyte: composed of lithium salt (LiPF6), solvent (EC / DMC / DEC) and additives;
[0063] Current collector: The positive electrode uses the above electrolyte-resistant composite aluminum foil, and the negative electrode is 6μm copper foil;
[0064] Binder: polyvinylidene fluoride (PVDF);
[0065] Conductive agent: carbon black or conductive graphite;
[0066] Solvent: N-methyl-2-pyrrolidone (NMP);
[0067] Step 2: Slurry preparation:
[0068] The positive or negative electrode active material is mixed with a binder and a conductive agent, and an appropriate amount of solvent is added and stirred to form a slurry;
[0069] Step 3: Coating:
[0070] Use a coating machine to evenly coat the slurry on the aluminum foil (positive electrode) or copper foil (negative electrode) to form a pole piece;
[0071] Step 4: Drying:
[0072] The coated electrode is dried in an oven to remove the solvent and excess water;
[0073] Step 5: Compacting:
[0074] Compact the dried electrode to improve the density and conductivity of the electrode;
[0075] Step 6: Cutting and Slicing:
[0076] Cut the pole pieces according to the size requirements of the required battery; process the pole pieces, including welding the pole ears, etc.;
[0077] Step 7: Winding:
[0078] The positive electrode sheets, negative electrode sheets and separators are stacked alternately and rolled into a cylindrical core using a winding machine;
[0079] Step 8: Shelling and welding:
[0080] The rolled core is placed in the battery case; the corresponding contact points between the tabs and the battery case are welded;
[0081] Step 9: Injection:
[0082] Under the protection of inert gas, inject the electrolyte into the battery shell
[0083] Step 10: Sealing:
[0084] Seal the battery case to ensure that the electrolyte does not leak;
[0085] Step 11:
[0086] The battery after injection is charged for the first time to form a solid electrolyte interface (SEI);
[0087] Step 12: Aging and testing:
[0088] Perform aging treatment on the battery to stabilize the battery performance; perform capacity, internal resistance, cycle life and other tests on the battery;
[0089] Step 13: Capacity division and matching:
[0090] Divide the battery capacity according to its capacity and internal resistance to ensure the consistency of the battery pack; match the batteries to ensure the performance of the battery pack;
[0091] Step 14: Packaging:
[0092] Qualified batteries are packaged and prepared for testing.
[0093] Throughout the entire process, the cleanliness and humidity of the production environment, as well as the battery charging and discharging conditions, need to be strictly controlled to ensure battery safety and performance.
[0094] Electrolyte immersion test: The composite aluminum foil was immersed in an electrolyte containing 1000ppm water for 240h and its adhesion was tested; the details are as follows:
[0095] The 180° adhesive peeling method is used. The adhesive method is suitable for films with relatively low adhesion, that is, the adhesion between the film and the substrate must be less than the adhesion between the film and the adhesive. The volume shrinkage of the selected adhesive should be very small after curing. The peeling method is to bond an adhesive tape of a certain width to the surface of the film, and then apply tension to the adhesive tape at a certain angle. After pulling the adhesive tape off, the adhesion can be judged according to the peeling of the film. The specific steps are as follows: prepare a composite aluminum foil sample with a width of 25mm and a length of 150mm, and use a 4.5lb roller to fully compact the tape to ensure good adhesion; place the bonded tape and sample for a period of time and let it stand to ensure that the adhesion between the tape and the film on the sample is fully stable; use an electronic tensile testing machine to perform a peeling test, and the peeling speed is 100mm / min±5mm / min; each group of samples is tested three times and the average value is taken, and this value is recorded as the initial value; after testing the initial value, the sample is immersed in the electrolyte for 240h, and then the sample is re-prepared to test its peeling force, and this value is recorded as the test value.
[0096] The specific data of materials and film thicknesses of the flexible substrate 1, the base layer S1, the first conductive layer S2, the first barrier layer S3, the second conductive layer S4, the second barrier layer S5 and the final third conductive layer S6 of Examples 1 to 7 and Comparative Example 1 are shown in Table 1, and the test results are shown in Table 1.
[0097] Table 1 Examples 1 to 7, Comparative Example 1
[0098]
[0099] As shown in Table 1, it can be seen from Examples 1 to 5 that the use of this structure can greatly improve the service life of the battery; in Example 6, due to the excessive thickness of Al2O3, the conductivity of the composite aluminum foil is poor and the internal resistance of the battery is too high, causing the battery to generate too much heat during the cycle life test, resulting in a rapid decline in life; in Example 7, due to the use of SiO2 as a base layer, the bonding strength with the substrate after immersion in the electrolyte is poor, and the test result is quite different from that of the Al2O3 base layer.
[0100] In summary, the utility model has a simple structure, reasonable design and the following advantages:
[0101] (1) A base layer 2 is provided between the flexible substrate 1 and the conductive layer 3. The base layer 2 provides a surface suitable for thin film growth for the conductive layer 3, which is helpful for nucleation and growth of the conductive layer 3. The base layer 2 can promote uniform growth of the conductive layer 3 and improve the crystal quality of the conductive layer 3; at the same time, it can also effectively prevent environmental factors from affecting the internal structure of the flexible substrate 1;
[0102] (2) A barrier layer 4 is provided between two adjacent conductive layers 3. The barrier layer 4 can help regulate the stress distribution in the flexible substrate 1. By interrupting the grain growth, the grain refinement of the conductive layer 3 is promoted, and the grain boundary size of the conductive layer 3 is increased, thereby dispersing the internal stress of the conductive layer 3, thereby reducing the defects caused by stress concentration. At the same time, since the lattice constants of the barrier layer 4 and the conductive layer 3 are different, the residual stress of the conductive layer 3 can be effectively adjusted by optimizing the material, thereby reducing the performance degradation of the conductive layer 3 caused by stress. After adding the barrier layer 4, the grain size of the overall conductive layer 3 is smaller and there are more grain boundaries, which can improve the resistance of the electrolyte-resistant composite aluminum foil to corrosive environments.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the utility model, rather than to limit it. Although the utility model has been described in detail with reference to the aforementioned embodiments, ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the utility model.
Claims
1. An electrolyte-resistant composite aluminum foil, characterized in that: It comprises a flexible substrate (1), wherein a plurality of conductive layers (3) are symmetrically arranged on the upper and lower sides of the flexible substrate (1), and a barrier layer (4) is arranged between two adjacent conductive layers (3); The thickness of the flexible substrate (1) is 3 to 20 μm, the thickness of the conductive layer (3) is 200 to 400 nm, and the thickness of the barrier layer (4) is 1 to 10 nm; The flexible substrate (1) is one of a biaxially oriented polypropylene film, a cast polypropylene film, a polyethylene terephthalate film, a polyimide film and a polyethylene naphthalate film; The conductive layer (3) is one of a metal aluminum layer, an aluminum-silicon alloy layer, an aluminum-copper alloy layer, an aluminum-magnesium alloy layer and an aluminum-zinc alloy layer; The barrier layer (4) is one or at least two of a metal nickel layer, a metal chromium layer, a nickel-chromium alloy layer, a metal titanium layer, a titanium alloy layer, and an aluminum oxide layer.
2. The electrolyte-resistant composite aluminum foil according to claim 1, characterized in that: It also includes a base layer (2), which is arranged between the flexible substrate (1) and the conductive layer (3); the base layer (2) has a thickness of 1 to 10 nm, and is an aluminum oxide layer.
3. The electrolyte resistant composite aluminum foil according to claim 1, characterized in that: The conductive layer (3) is a metal aluminum layer, and the thickness of the conductive layer (3) is 300-350 nm.
4. The electrolyte resistant composite aluminum foil according to claim 1, characterized in that: The barrier layer (4) is a nickel-chromium alloy layer.
5. The electrolyte resistant composite aluminum foil according to claim 1, characterized in that: Three conductive layers (3) are symmetrically arranged on the upper and lower sides of the flexible substrate (1).
6. A current collector, characterized in that: The invention comprises a positive electrode and a negative electrode, wherein the positive electrode is the electrolyte-resistant composite aluminum foil as claimed in any one of claims 1 to 5, and the negative electrode is a copper foil with a thickness of 6 μm.
7. A battery, characterized in that: Comprising the current collector as claimed in claim 6.